2015
DOI: 10.1097/med.0000000000000190
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and the thyroid

Abstract: Adequate nutritional supply of selenium that saturates expression of circulating selenoprotein P, together with optimal iodine and iron intake, is required for a healthy and functional thyroid during development, adolescence, adulthood and aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
68
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 164 publications
(84 citation statements)
references
References 133 publications
1
68
0
10
Order By: Relevance
“…4 An alternative explanation highlights the effects of selenium on the immune system, postulating that selenium deficiency likely constitutes a risk factor for a feed-forward derangement of the derailed immune system-thyroid interaction in AITD. 5,6 Furthermore, selenium is an essential part of the iodothyronine deiodinase (DIO) enzymes, and selenium deficiency is followed by a decreased conversion of thyroxine (T4) to the active hormone triiodothyronine (T3). This interaction hasas far as we knownever been observed in humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 An alternative explanation highlights the effects of selenium on the immune system, postulating that selenium deficiency likely constitutes a risk factor for a feed-forward derangement of the derailed immune system-thyroid interaction in AITD. 5,6 Furthermore, selenium is an essential part of the iodothyronine deiodinase (DIO) enzymes, and selenium deficiency is followed by a decreased conversion of thyroxine (T4) to the active hormone triiodothyronine (T3). This interaction hasas far as we knownever been observed in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Both cell-mediated and the humoral immune response may be impaired in selenium deficiency, and it has been suggested that this effect of selenium deficiency is present already at mild and moderate selenium deficiency. 5,6 In Denmark, selenium deficiency appears not to be a general problem. 7 The aim of our study was to evaluate signs of selenium deficiency in patients with autoimmune thyroid disease by comparing serum selenium (s-Se) values in patients with newly diagnosed Graves' disease (GD), autoimmune overt hypothyroidism (AIH) and controls from the Danish population.…”
Section: Introductionmentioning
confidence: 99%
“…Se is an essential micronutrient that is incorporated into biologically active selenoproteins as the amino acid selenocysteine [3]. Among the most important are the iodothyronine deiodinases that are directly involved in thyroid hormone metabolism [3]. In healthy euthyroid individuals with marginal Se deficiency, Se supplementation has only minute, and clinically insignificant, effects on thyroid function [4].…”
mentioning
confidence: 99%
“…Se is an essential micronutrient that is incorporated into biologically active selenoproteins as the amino acid selenocysteine [3]. Among the most important are the iodothyronine deiodinases that are directly involved in thyroid hormone metabolism [3].…”
mentioning
confidence: 99%
“…The thyroid gland is characterized by higher tissue concentrations of selenium than any other organ, which suggests its crucial role in proper thyroid function. 1 This finding is supported by the fact that selenium stimulates conversion of thyroxine to triiodothyronine, reduces free radical production, and exerts antiinflammatory and immune-suppressive effects. [2][3][4] In numerous studies selenium, administered alone or in combination with levothyroxine, reduced thyroid antibody titers and decreased thyroid hypoechogenicity in patients with Hashimoto thyroiditis (autoimmune thyroiditis).…”
mentioning
confidence: 95%